Distribution of plasminogen activator inhibitor in normal liver, cirrhotic liver, and liver with metastases. Issue 3 (March 1994) - Fitch, P; Bennett, B; Booth, N A; Croll, A; Ewen, S W
Abstract : AIMS--To examine the distribution of PAI-1 antigen in normal and cirrhotic liver and liver with metastases. METHODS--Sections of normal and cirrhotic liver and liver with metastases were stained using the alkaline phosphatase antialkaline phosphatase (APAAP) technique and monoclonal antibody specific for plasminogen activator inhibitor (PAI-1). RESULTS--PAI-1 antigen was identified as discrete granules in the cytoplasm of hepatocytes in normal liver, particularly around portal tracts and central veins of the liver lobule. In cirrhotic liver a striking reduction of PAI-1 antigen was noted. In liver with metastases increased amounts of PAI-1 antigen were concentrated in hepatocytes around the margins of malignant deposits. CONCLUSIONS--Cirrhotic liver contains considerably less PAI-1 antigen than does normal liver, despite raised plasma concentrations of PAI-1. This may reflect release of hepatic PAI-1 into the circulation or decreased clearance of PAI-1 from the plasma. Secondary malignant deposits in the liver seem to stimulate production of PAI-1 in adjacent hepatocytes. This may influence the invasive process and may contribute to the thrombotic tendency associated with malignancy.